2020
DOI: 10.1029/2020jc016061
|View full text |Cite
|
Sign up to set email alerts
|

Source Versus Recycling Influences on the Isotopic Composition of Nitrate and Nitrite in the East China Sea

Abstract: Nitrogen transfer processes and NO3− sources in the East China Sea (ECS) were analyzed using dual isotopes of NO3− and NO2−, the concentration and isotopes of dissolved O2 and N2 gases, nutrient concentrations, and the hydrological conditions. It was clear that the δ15N and δ18O values of NO3− in the Changjiang freshwater were 5.6–6.6‰ and 0.6–1.0‰, respectively, affected by human activities (fertilizer, sewage, and manure) and nitrification. Off the Changjiang Estuary to the ECS continental slope, the NO3− co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 129 publications
(261 reference statements)
3
6
0
Order By: Relevance
“…This argument is supported by recent findings that the ammonia monooxygenase (amoA) genes are abundant in the upper water column (50–75 m, Hu et al., 2011) and the AOA is dominant oxidizers of NH 3 in the SCS (Hou et al., 2018). In addition, the fact that the NO 2 − in the PNMs of the NSCS mainly comes from NH 3 oxidation is similar to those found in the East China Sea (Liu et al., 2020), the Arabian Sea (Buchwald & Casciotti, 2013), the central California Current (Santoro et al., 2013), the Sargasso Sea (Newell et al., 2013), the Eastern Tropical North Pacific (Peng et al., 2015), the Gulf of Aqaba (Mackey et al., 2011) and the Ross Sea (Olson, 1980b), which highlights the importance of NH 3 oxidation in the formation of PNM in global ocean.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This argument is supported by recent findings that the ammonia monooxygenase (amoA) genes are abundant in the upper water column (50–75 m, Hu et al., 2011) and the AOA is dominant oxidizers of NH 3 in the SCS (Hou et al., 2018). In addition, the fact that the NO 2 − in the PNMs of the NSCS mainly comes from NH 3 oxidation is similar to those found in the East China Sea (Liu et al., 2020), the Arabian Sea (Buchwald & Casciotti, 2013), the central California Current (Santoro et al., 2013), the Sargasso Sea (Newell et al., 2013), the Eastern Tropical North Pacific (Peng et al., 2015), the Gulf of Aqaba (Mackey et al., 2011) and the Ross Sea (Olson, 1980b), which highlights the importance of NH 3 oxidation in the formation of PNM in global ocean.…”
Section: Discussionsupporting
confidence: 79%
“…In order to reveal the formation mechanism of the PNM, natural abundance N and oxygen (O) isotopes of NO 2 − is a direct and powerful tool because it opens a new window and imprints a unique signal on NO 2 − cycling in the ocean (Buchwald & Casciotti, 2013). The dual isotopes of NO 2 − has provided valuable information for the formation of PNM in marine environment (Buchwald & Casciotti, 2013; Buchwald et al., 2015; Liu et al., 2020). Similar to the case of the PNM, NO 2 − isotopic signatures have been also used to reveal N transformation processes in the SNM (Bourbonnais et al., 2015; Buchwald et al., 2015; Casciotti & McIlvin, 2007; Casciotti et al., 2013; Gaye et al., 2013; Hu et al., 2016; Martin & Casciotti, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because neither phytoplankton assimilation nor mixing with other water masses from surrounding water would be significant enough to cause δ 18 O-NO 3 − values greater than 10‰ (Ye et al, 2016). Similar studies were found in Xiangshan bay (Yang et al, 2018), East China Sea (Liu et al, 2020), northern South China Sea (Kao et al, 2012;Lao et al, 2019;Wong et al, 2002;Ye et al, 2015), which also suggested that the important nitrate source from atmospheric deposition in the marine system.…”
Section: Elevated Nitrate Dual Isotope Values Due Mainly To Assimilat...supporting
confidence: 80%
“…The accumulation of NO 2 − in the euphotic zone is called the primary NO 2 − maximum (PNM, Dore & Karl, 1996; Kiefer et al., 1976; Lomas & Lipschultz, 2006; Olson, 1980b), which is one of the typical features of NO 2 − in an aerobic environment. For decades, interdisciplinary approaches have been used to address the mechanisms of PNM formation in various marine environments, including stable isotopic geochemistry (Buchwald & Casciotti, 2013; Chen et al., 2021; Liu et al., 2020; Mackey et al., 2011; Olson, 1980a; Peng et al., 2015; Santoro et al., 2013; Ward et al., 1984), geochemical models (Kiefer et al., 1976; Zakem et al., 2018), microbiology (Horrigan et al., 1981; Guerrero & Jones, 1996a, 1996b; Zakem et al., 2018), and phytoplankton research (Kiefer et al., 1976; Milligan & Harrison, 2000; Vaccaro & Ryther, 1960). Although two main mechanisms for PNM formation, namely NH 3 oxidation and NO 3 − reduction, have been proposed (Lomas & Lipschultz, 2006), there are still some questions to be addressed regarding the formation of PNM.…”
Section: Introductionmentioning
confidence: 99%
“…The response of the Arctic Ocean to climate change has been rapid and dramatic, resulting in warmer (Huang et al., 2017; Miller et al., 2013), desalinated (Notz & Stroeve, 2016; Peterson et al., 2002) and more stratified waters (McLaughlin & Carmack, 2010; Toole et al., 2010). However, current studies on the formation of PNM are limited to mid‐ and low‐latitude oceans (Buchwald & Casciotti, 2013; Chen et al., 2021; Liu et al., 2020; Newell et al., 2013; Santoro et al., 2013; Ward et al., 1982; Zakem et al., 2018), and studies on the Arctic Ocean are lacking. Uncovering the NO 2 − cycle in the Arctic Ocean under Arctic warming is important for understanding the formation and possible changes of oceanic PNMs.…”
Section: Introductionmentioning
confidence: 99%